Engaging with capitalism cases from Oceania - McCormack, Fiona, 1970-; Barclay, Kate (Research in economic anthropology ;, 2013)
For several decades people have been grappling with how to retain the material safety and cultural richness of indigenous non-capitalist societies and economies, but also gain the health, wealth, education and life opportunities the modern capitalist world offers. This book brings together examples of attempts to forge locally appropriate versions of modernity; development that suits the aspirations and circumstances of particular groups of people. Authors question how the market economy has been variously negotiated by groups who also have other systems through which they organize their social and economic life. What has worked for these people, what has not, and why? The volume addresses how, as a social and economic system, capitalism has been very effective in generating wealth and technological innovation, but has also been associated with great social inequity and environmental damage. Its inherent flaws have been highlighted by the escalation of ecological problems arising from growth-oriented capitalism and various economic crises, the latest being the Global Financial Crisis and its ongoing fallout.